MEMS FABRICATION USING 2PP TECHNIQUE BASED 3D PRINTER - (:unkn) unknown (My University, 2020)
This study aims to fabricate Electro-Thermal Micro Actuator with a support structure by using the Two-Photon Polymerization (2PP) technique based 3D printer. This study was carried out with the 3D printer which is possible to fabricate the actuator which can be fabricated by the traditional Micro Electro Mechanical System (MEMS) methods. Due to the high cost of traditional MEMS methods, difficult and excessive processing, many studies have been carried out for new fabrication methods. 2PP is the most widely used and developed method of production. With this method, direct fabrication up to nano level is possible. Also, many chemical processes used in traditional methods will not be applied using 2PP based 3D printers. The design of the bi-directional movable Electro-Thermal Micro Actuator is carried out in this study. Supporting structures with a diameter of 2 microns allow the Actuator to be fabricated without breakage. 2PP method of the 2-micron length of the very easy and low-cost production was seen in this study. Thanks to this method, traditional MEMS production methods will be replaced by 3D printers in the following years.